Penegakan Hukum Pidana Terhadap Kasus Kenakalan Remaja di Kabupaten Purbalingga - Yusdinsyah, Dwi Anugrah; Widodo, Selamat (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
Purbalingga Regency is currently facing serious challenges related to social security and safety due to increasing criminal activities involving groups of teenagers. This study aims to determine and analyze criminal law enforcement against juvenile delinquency cases in Purbalingga Regency, and to determine and analyze the obstacles for the Purbalingga Regency police so that crimes committed by juveniles do not occur. The type of research uses empirical legal research, with a descriptive research nature. The location of the research is at the Purbalingga Police. The types and sources of data in the study consist of two types, primary data and secondary data. Data collection techniques are by observation, interview, and literature study techniques. The data analysis technique is qualitative. The results of this study are criminal law enforcement against juvenile delinquency cases in Purbalingga Regency, namely carried out systematically by prioritizing aspects of protection and guidance based on applicable laws and regulations, and free sales. The obstacles for the police in following up so that crimes committed by juveniles do not occur are in external factors, namely the lack of involvement and responsibility from parents. In various cases, after the child is secured by the police, the parents should be present to provide assistance or pick up